2010
DOI: 10.1007/s00198-010-1385-0
|View full text |Cite
|
Sign up to set email alerts
|

Impaired fracture healing in macrophage migration inhibitory factor-deficient mice

Abstract: The results of the present study suggest that delayed fracture healing in MIF KO was mainly attributable to a delay in osteoid mineralization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 35 publications
1
21
1
Order By: Relevance
“…Our findings are in line with those of all other papers on this area[21-23,46], other than Jacquin et al and Mun et al . There are key differences between the current study and that Jacquin et al .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our findings are in line with those of all other papers on this area[21-23,46], other than Jacquin et al and Mun et al . There are key differences between the current study and that Jacquin et al .…”
Section: Discussionsupporting
confidence: 94%
“…MIF -/- mice exhibit protection from bone loss induced by ovariectomy[21] and periodontal disease[22]. MIF -/- mice show lower osteoclast numbers at fracture callus[23], and elevated bone resorption is seen in MIF transgenic mice[24]. However, Jacquin et al [25] have reported the converse, that MIF reduced osteoclastogenesis in vitro , and that MIF -/- mice have significantly reduced trabecular bone mass.…”
Section: Introductionmentioning
confidence: 99%
“…Radiographs of the right and left femurs were taken at 2, 4, and 6 weeks after fracture by using an X-ray unit (SkyScan 1074, Toyo Co., Tokyo, Japan). The callus area at the fracture site was measured at 2 weeks after fracture because this area is known to peak at this time point in mice [1], [2]. The degree of callus formation was calculated as the ratio of the callus area to the femoral bone diameter at the fracture gap [16].…”
Section: Methodsmentioning
confidence: 99%
“…Bone regeneration after fracture occurs in the following consecutive phases: callus formation around the fracture site, osteoid formation, mineralization within the callus, and callus resorption [1], [2]. Although the molecular mechanisms underlying these phases are not fully understood, impairment of callus formation is known to delay fracture healing [2]. Mineralization of the osteoid, an essential component of the fracture healing process is regulated by alkaline phosphatase (ALP) [3].…”
Section: Introductionmentioning
confidence: 99%
“…M2b have also been found in circulation and peripheral tissues following severe burns, supporting a systemic activity for this subset [40,41].…”
Section: Disease Associationsmentioning
confidence: 73%